Evaluating Entrepreneurial Features of Firm’s Growth Using Confirmatory Factor Analysis - M, Arthur-Aidoo B; C, Aigbavboa; D, Thwala W (Journal of Economics and Behavioral Studies, 2017)
The growth of Small and medium-size firms cannot ensue without the entrepreneurial features and the environment that the firm operates. The entrepreneurial characteristics, therefore, are vital due to the unique individualism of firm owners or sponsors. Construction SME growth-oriented firms are a significant contributor to Ghana’s economic gain. Conversely, the concept of growth varies from one entrepreneur to the others depending on the exhibited skills by the entrepreneurs, hence entrepreneurial features. Numerous factors influence the entrepreneurial features as a factor of firmâ€™s growth. Some are of the factors are established and categorised as having strong influence while others are classified weak. This study, therefore, adopted the confirmatory factor analytical technique to justify the factors after exploring. To achieve the goal of the study, respondents such as firm owners, SME managers and construction professionals engaged by SMEs as the population were administered with questionnaires. In all, 315 questionnaires were given out in the form of semi-structured structured, but only 228 were retrieved for analysis representing a responds rate of 72 percent. The study established Cronbach alpha and composite reliability values that predicted the entrepreneurial feature as a subsequent determinant of firmâ€™s growth. Additionally, the hypothesis was supported statistically suggesting that there is a direct relationship between entrepreneurial features and firm growth.